Clinical Implications of a New TSH-receptor-antibody-assay (DYNOtest® TRAKhuman) in Autoimmune Thyroid Diseases - Meller, J.; Schreivogel, I.; Bergmann, A.; Morgenthaler, N.; Hüfner, M.; Becker, W. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: Conventional radioreceptor-antibody-assays (RAAs) fail in the detection of TSH-receptor antibodies (TRAKs) in 10–30% of patients with Graves’ disease (GD). The aim of this study was the evaluation of the diagnostic and clinical impact of a new RRA (DYNOtest® TRAKhuman) which uses the human recombinant TSH-Receptor in the diagnosis of autoimmune thyroid disease. Methods: Sera from 142 consecutive patients (GD: n=50, autoimmune thyroiditis/AIT: n=92) and from 55 controls (31 patients without any thyroid disease and 14 with euthyroid goiter) were evaluated both with the DYNOtest® TRAKhuman-assay and a conventional RRA (TRAK-Assay®). Thyroid in vitro parameters and thyroid sonography were performed in all patients. Results: The DYNOtest® TRAK-assay was significantly superior to the conventional RRA in the diagnosis of GD (p < 0,00012), especially in those who were treated by thionamides (p < 0,003) and in the diagnosis of TRAK-positive patients with AIT(p < 0,003). The majority of TRAK-positive AIT-patients suffered from hypothyroidism. One false positive result in patients with euthyroid goiter was found in the TRAK-Assay® as well as in the DYNOtest® TRAKhuman-Assay. Therefore the specifity of the DYNOtest® TRAKhuman was not inferior compared with the conventional assay. Conclusion: The DYNOtest® TRAK-assay is superior in the diagnostic work up of Graves’ disease compared with a conventional TRAK-assay and offeres an equal specifity.
Keywords: Autoimmune thyroid diseases; Graves’ disease; autoimmune thyroiditis; IRAK; radioreceptorassay; thyroid scintigraphy